'I had to work through what people would think of me': negotiating 'problematic single motherhood' as a solo or single adoptive mum. Issue 1 (2nd January 2023) - Mackenzie, Jai
ABSTRACT: This article considers how five single mothers, who used adoption or donor conception to bring children into their lives, negotiate a persistent and pervasive discourse of 'problematic single motherhood' in their interview talk. Tactics of intersubjectivity (Bucholtz & Hall [2005]. Identity and interaction: A sociocultural linguistic approach. Discourse Studies, 7(4–5), 585–614.), especially the overlapping strategies of distinction, authorisation and illegitimation, are shown to be particularly salient for these parents, as they work to legitimise their routes to motherhood by distancing themselves from widely stigmatised positions such as young motherhood, working-class motherhood and unplanned motherhood. I argue that these single women's intersubjective positioning serves to protect them against stigma and discrimination, but often relies on the reproduction of other polarising and discriminatory discourses, which feed into idealised constructions of mothers as responsible, middle-class, and appropriately aged citizens. Overall, the analysis suggests that it is difficult for these single mothers to challenge the multiple and intersecting discriminatory discourses, ideals and stereotypes that converge in exclusionary and limiting constructions of single motherhood, whilst maintaining a recognisably legitimate social position for themselves.